If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -100 = 0 Reorder the terms: -100 + 10x = 0 Solving -100 + 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '100' to each side of the equation. -100 + 100 + 10x = 0 + 100 Combine like terms: -100 + 100 = 0 0 + 10x = 0 + 100 10x = 0 + 100 Combine like terms: 0 + 100 = 100 10x = 100 Divide each side by '10'. x = 10 Simplifying x = 10
| (2r^-1s^2t^0)^-2/2rs | | 13-(-9)=x | | 9x^4-9x^3-225x^2-225x=0 | | 2.1x+5=49.10 | | -3(4x+3)+2(5x-8)= | | 24=2t+5t^2 | | -2(7w-7)+w=5(w+4) | | (8b-10)-2(6-3b)= | | 1.29x+21+0.99=15 | | (4p-8)+(6p-7)= | | 2x+7-5=-17 | | 18x+1=15x+10 | | Sin(x)/2x | | 8-2(3y+5)= | | x^2-4x+70=0 | | -y+15=241 | | 6f+3(f+9)= | | 5x-(4)-2y+z=0 | | 3(u-9)=-54 | | (3x×sinx)/2x=sin40 | | -2(y+4)+4(2y+5)= | | 7(x+2)-6= | | 4n=2*12 | | x^2+y^2=3x-4y | | -3(y+5)-2y= | | 20=-5/2u | | -(x+1)-1= | | -(-y-4w+3)= | | (3y)=x-2x | | -5(-1)(-3)(-3)= | | 6(11-2)=54 | | P+9=56 |